Hemoglobin E in Northeast India: A review on its origin, distribution, migration and health implication - Sikdar, Mithun (Anthropological Review, 2016)
A systematic review of the studies on hemoglobin E in Northeast India has been carried out to understand the magnitude of research undertaken on this aspect during the last seven decades. Owing to the high prevalence of hemoglobin E in this part of India different authors have studied this hemoglobin from different perspectives and found conflicting results. However a systematic review of such studies is lacking from a holistic point of view. Most of the epidemiological, in vitro as well as in vivo studies show signatures of selection with this hemoglobin locus. However, how this polymorphism is maintained at different rates at different geographical region is still a matter of contention. This review will fill the gap from all perspectives starting from the frequency distribution of hemoglobin E and its spread in different parts of Northeast India, its relationship with malaria hypothesis, the population migration, population affinity and most importantly the health implication arising out of it. A probable origin of hemoglobin E among an Austroasiatic population of Northeast India has been postulated with the help of advance molecular anthropological knowledge like the deep rooted markers of mt DNA and Y-chromosome haplotypes.